Patterns and prevalence of dyslipidemia in patients with different etiologies of chronic liver disease - Unger, Lukas W. (Wien Klin Wochenschr, 2019)
BACKGROUND: Liver disease impacts on hepatic synthesis of lipoproteins and lipogenesis but data on dyslipidemia during disease progression are limited. We assessed the patterns of dyslipidemia in (i) different liver disease etiologies and discriminated (ii) non-advanced (non-ACLD) from advanced chronic liver disease (ACLD) as it is unclear how progression to ACLD impacts on dyslipidemia-associated cardiovascular risk. METHODS: Patients with alcoholic liver disease (n = 121), hepatitis C (n = 1438), hepatitis B (n = 384), metabolic/fatty liver disease (n = 532), cholestatic liver disease (n = 119), and autoimmune hepatitis (n = 114) were included. Liver stiffness ≥15 kPa defined ACLD. Dyslipidemia was defined as total cholesterol >200 mg/dL, low-density lipoprotein (LDL)-cholesterol >130 mg/dL and triglycerides >200 mg/dL. RESULTS: Across all etiologies, total cholesterol levels were significantly lower in ACLD, when compared to non-ACLD. Accordingly, LDL-cholesterol levels were significantly lower in ACLD due to hepatitis C, hepatitis B, metabolic/fatty liver disease and autoimmune hepatitis. Triglyceride levels did not differ due to disease severity in any etiology. Despite lower total and LDL cholesterol levels in ACLD, etiology-specific dyslipidemia patterns remained similar to non-ACLD. Contrary to this “improved” lipid status in ACLD, cardiovascular comorbidities were more prevalent in ACLD: arterial hypertension was present in 26.6% of non-ACLD and in 55.4% of ACLD patients (p < 0.001), and diabetes was present in 8.1% of non-ACLD and 25.6% of ACLD patients (p < 0.001). CONCLUSION: Liver disease etiology is a major determinant of dyslipidemia patterns and prevalence. Progression to ACLD “improves” serum lipid levels while arterial hypertension and diabetes mellitus are more prevalent. Future studies should evaluate cardiovascular events after ACLD-induced “improvement” of dyslipidemia. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00508-019-01544-5) contains supplementary material, which is available to authorized users.